Alcohol use and its influencing factors among undergraduate students in Uttar Pradesh University of Medical Science in district Etawah, India - Mehra, Jyoti; Nayak, Kripashankar; Jain, Pankaj Kumar; Srivastava, Dhiraj; Kharya, Pradip; Sachan, Neha (International Journal Of Community Medicine And Public Health, 2018)
Background: Alcohol is most widely used substance abuse in college students. Use of alcohol is common in both urban as well as in rural area. In our country, there are many influencing factor for Alcohol use like peer pressure, friends, family and social media etc. Alcohol use has also effect on personal level, family as well as our society. So keeping these facts in view, the above mentioned study is being conducted. Aim of the study is to assess the use of alcohol among college going students and to find out factors influencing alcohol use. The study of objectives was done to assess the use of alcohol among college students, to correlate alcohol, use with socio-demographic profile of students and assessment of factors leading to use of alcohol. Methods: The Present study was college based cross sectional study carried out in UP University of Medical Sciences, Saifai, Etawah for a period of one month in January2017. Consent from dean of the college was taken. A total of two hundred undergraduate students were randomly selected as study subjects. Results: Out of total two hundred participants, majority were male. Prevalence of alcohol use in this study was 20%. Most of the participants use alcohol on monthly basis (i.e. 55% and most of them (i.e. 80%) were influenced by their friends to take alcohol. Among them 61% was using alcohol for fun. Conclusions: Parents should have the responsibility for increasing communication with their children. There are need to support the students by fathers and mothers to lower the regular alcohol drinking habit.